The Impact of Workforce Diversity on Organizational Performance: A Review - Rafaqat, Simon; Rafaqat, Sahil; Rafaqat , Saoul; Rafaqat , Dawood (Journal of Economics and Behavioral Studies, 2022)
The paper aims to review the literature on the effect of workforce diversity including, gender, culture/race, age, and ethnicity, on firm performance. Many empirical papers have been reviewed in which different statistical models have been applied to data of multiple types of organizations across the regions and continents to find the association between the selected variables. The review methodology is selected to survey the literature on the impact of workforce diversity on organizational performance between the years 2000 and 2021. The reviewed literature shows that workforce diversity is significantly related to organizational performance. Moreover, this paper concludes that the positive significant influence of workforce diversity on organizational performance exceeds the negative significant impact. Also, workforce diversity is productive, if it is in appropriate balance. Whereas few studies reported no significant influence of workforce diversity on organizational performance.